Drug Resistance Mechanism of Enterobacteriaceae with Decreased Antibiotic Sensitivity - Fang Rong; Yuanyuan Sun; Xiao Li; Chenhao Zhang (Applied Bionics and Biomechanics)
To investigate the mechanism of antibiotic resistance in Enterobacteriaceae. Carbapenem Enterobacteriaceae bacteria isolated from a hospital from January 2015 to June 2020 were selected. Drug resistance phenotype test, drug sensitivity test, and conjugation test were used to observe the drug sensitivity results and the titer of acrB antibody. Finally, the data were statistically analyzed. All strains were resistant to ceftazidime, ceftriaxone, ertapenem, and aztreonam. 87.5% of the samples were resistant to piperacillin. Multisite sequence typing showed that 5 carbapenem-resistant Klebsiella pneumoniae belonged to 4 different types. The sequence types of kpn6099 and kpn6617 were the same. In the sensitivity comparison, Escherichia coli J53 was more sensitive to these two antibiotics, minimum inhibitory concentration values were 0.5 and 0.25 μg/ml, respectively. In addition, the sensitivity of E. coli J53 to carbapenems was slightly higher than that of kpn6617. The results showed that the enzyme-linked immunosorbent assay titer of acrB antibody was 1:40,000, and the preparation of acrB antibody was successful. Plasmid-mediated deletion of IMP-1 metallo-β-lactamase binding outer membrane protein is one of the main reasons for the decrease of antibiotic sensitivity.